Impact of Chemically Engineered Biochar on Stabilization of Arsenic in an Acid Soil - Singh, Swati; Purakayastha, T. J.; Kumar, Sarvendra; Dey, Saptaparnee; Golui, Debasis; Datta, Anindita; Mandloi, A. S.; Garg, Atul (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during June, 2024–August, 2025 at the division of Soil Science and Agricultural Chemistry ICAR-IARI, New Delhi, India to investigate the efficacy of chemically engineered biochars for remediating arsenic (As)-contaminated soils and reducing its uptake by rice. Engineered biochars were produced from rice straw (RBC), sugarcane bagasse (SBC), and jute stalk (JBC) by chemical modifications with FeCl3, goethite (FeOOH), and magnetic iron oxides. Initial screening in an As-spiked acidic Inceptisol from Assam demonstrated a strong dose-dependent immobilization effect. The FeCl3-modified biochars, particularly those from rice straw (RBC-FeCl3) and sugarcane bagasse (SBC-FeCl3), achieved the highest arsenic immobilization efficiencies, up to 81.0%, at an application rate of 6.70 g kg-1 soil. Detailed sorption-desorption studies revealed that SBC-FeCl3 exhibited the maximum adsorption capacity and strongest binding affinity for As, characterized by high Freundlich adsorption intensity and significant positive hysteresis (Desorption Index>1), indicating stable, long-term retention. Superior performance was attributed to the formation of reactive iron oxide phases (akaganéite and hematite) on the biochar surface, as confirmed by XRD and FTIR analyses. A net house pot experiment with rice (Oryza sativa L., cv. Ranjit) showed that SBC-FeCl3 application (6.67 g kg-1) significantly reduced extractable soil As by 46% and lowered As concentration in rice straw by 64% compared to the control. The study concluded that FeCl3-engineered biochar, especially SBC-FeCl3, was a highly effective, dual-benefit strategy for immobilizing arsenic in acidic soils and mitigating its transfer into the food chain.